PENGEMBANGAN KERJA PEGAWAI CU BIMA - Atong, Petrus (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
Work development for employees of Bina Masyarakat Credit Union branch Sungai DurianSintang is carried out to know, understand, study and develop aspects of employee empowerment, workrewards, work compensation and employee work ethic. The research method is descriptive qualitative, theresearch subjects consist of branch managers and staff employees. The research instrument consists ofinterviews, documentation and observation. Data analysis is qualitative analysis. The results of theresearch concluded that empowerment, rewards and compensation had been carried out in accordance withthe provisions of management policy patterns and personnel regulations, then regarding work ethicinformation was obtained that employee work results were in accordance with standard provisions forwelfare acceptance. The research results also found that there are other aspects that also determine employeework development, namely those relating to employee work discipline. The suggestions made so thatemployee work development can be better are seen as needing to be further supported by work enthusiasmand increased employee discipline at work